Equality and Openness in Confucian-Christian Dialogue: A Review of Professor Wang Zhijun’s Comparative Study of Mencius and Paul on the Ethics of Life and Death - ZHENG, Xianru (Journal of Research for Christianity in China (JRCC), 2024)
Wang Zhijun, A Comparative Study of the Ethics of Life and Death in Mencius and Paul, Shanghai: Shanghai Sanlian Books, 2024 edition.